Optimalisasi Rute Distribusi Songkok Untuk Meminimalkan Biaya Transportasi Pada CV. ABC - Bagus Wahyudi; Hilyatun Nuha (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
CV. ABC is a manufacturing industry producing songkok that serves nine regular customers across East Java and Madura. Currently, the company faces transportation cost inefficiencies due to the implementation of a rigid zone-based distribution system. This condition leads to suboptimal fleet capacity utilization and inflated travel distances, resulting in total transportation costs of Rp3,486,700 per delivery period. This study aims to determine a more optimal distribution route to minimize travel distance and identify concrete cost savings comparisons.  The method employed in this research is the Vehicle Routing Problem (VRP) using a Mixed Integer Linear Programming (MILP) mathematical model approach. The data processing and search for the optimal route were executed using Python software via the Google Colab platform. The research results indicate that the proposed route successfully reduced the total distribution distance from 2,026 km to 1,234 km, equivalent to a distance saving of 39%. Furthermore, significant financial efficiency was achieved, where total monthly operational expenditures decreased from Rp45,574,150 to Rp32,234,850.